History, Status, and Taxonomic Identity of Caribou (Rangifer tarandus) in Northwest Greenland - Roby, Daniel D.; Thing, Henning; Brink, Karen L. (ARCTIC, 1984)
Historical references indicate that caribou (Rangifer tarandus L.) numbers drastically declined throughout the Thule District during the early part of this century, and that the primary causes were: (1) the influx of polar explorers and their distribution of firearms to the Thule Eskimos which initiated extensive hunting pressure on caribou; and (2) a series of relatively mild, wet winters resulting in snow conditions which restricted access to forage and caused several catastrophic die-offs. No live caribou were seen during six hours of aerial surveys over Inglefield Land, Thule District, Northwest Greenland, during July 1978. No fresh caribou sign was found during five days of searching in the Rensselaer Bay area of Inglefield Land. Unless some individuals were not detected or subsequent emigration from Ellesmere Island has occurred, the Inglefield Land caribou population has been extirpated. The Thule District caribou population apparently originated from barren-ground caribou (R. t. groenlandicus Gmlin) which emigrated from Southwest Greenland, rather than from Peary caribou (R. t. pearyi Allen) from Ellesmere Island.Key words: caribou, Rangifer, Greenland, Thule District, Inglefield Land, High Arctic Mots clés: caribou, Rangifer, Groenland, district de Thule, terre d'Inglefield, nord de l'Arctique